2018
DOI: 10.1002/cnma.201800422
|View full text |Cite
|
Sign up to set email alerts
|

Robust Icephobic Performance of Flexible Needles

Abstract: Superhydrophobic micro‐/nanopatterned structures exhibit robust water/ice repellence in harsh environments, which is significant for theoretical study and industrial applications such as cooling in nuclear power, heat transfer, and self‐cleaning for aircraft. However, the reported studies regarding icephobic functional surfaces based on rigid materials have indicated potential dangers in applications, e. g., the roughness topographies are easily ruined in the icing process, which limits further application and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
(47 reference statements)
0
11
0
Order By: Relevance
“…In the previous research, we have found the flexible base is useful for enhancing the stability of nano‐structure on the surface. [ 37 ] It showed the energy generated by the impacting droplet or volume expansion of ice in the icing progress could be effectively transferred to the flexible base, resulting in enhancing the stability and duration of nano‐materials. However, by reducing the materials’ stiffness to improve its flexibility is easy to cause the loss of surfaces’ function, because the surface has a low load limit and a larger strain.…”
Section: Resultsmentioning
confidence: 99%
“…In the previous research, we have found the flexible base is useful for enhancing the stability of nano‐structure on the surface. [ 37 ] It showed the energy generated by the impacting droplet or volume expansion of ice in the icing progress could be effectively transferred to the flexible base, resulting in enhancing the stability and duration of nano‐materials. However, by reducing the materials’ stiffness to improve its flexibility is easy to cause the loss of surfaces’ function, because the surface has a low load limit and a larger strain.…”
Section: Resultsmentioning
confidence: 99%
“…Previous researches have confirmed that the rough topographies could provide much pocketed air between the solid‐liquid interface, which declines the contact area and leads the droplet roll off with small tilted angle . The flexible body is also a significant role for enhancing the durability of surface topographies . When the surface under loading, the external energy is mainly transferred into the elastic energy of the body, which decreases the overloading on the weak nano‐topography of the surface.…”
Section: Figurementioning
confidence: 99%
“…[31][32] The flexible body is also a significant role for enhancing the durability of surface topographies. [33] When the surface under loading, the external energy is mainly transferred into the elastic energy of the body, which decreases the overloading on the weak nano-topography of the surface. The MHCs in LD's wing play two significant roles, one is to keep the wing high-strength and lightweight, the other one is to transfer the stress from the surface into the interlayer of the wing.…”
mentioning
confidence: 99%
“…Based on these discoveries, other functional surfaces, including magnetic field-driven ferrofluids and oil-infused polymeric materials, have also been investigated (19)(20)(21). However, a robust surface design that is able to show a long-term resistance to ice accretion, especially when harsh operating conditions such as high humidity and mechanical wearing are present, still remains a challenge (22)(23)(24)(25).…”
mentioning
confidence: 99%